2021
DOI: 10.20414/iqtishaduna.v12i2.3457
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Rasio Keuangan Bank Pembiayaan Rakyat Syariah Sebelum Dan Selama Pandemi Covid-19

Abstract: Pandemi Covid-19 sudah memberikan akibat yang signifikan pada segala kehidupan manusia, seperti di bidang pendidikan, kesehatan, ekonomi, dan lain-lain. Metode yang dipakai dalam penelitian berupa penelitian kuantitatif dengan memakai data sekunder dan mengumpulkannya lewat metode dokumentasi serta dianalisis memakai statistik desktiptif dan independent sample t-test. Data yang diambil sebelum Covid-19 berupa rasio keuangan CAR, ROA, ROE, NPF, FDR, dan BOPO di Bank Pembiayaan Rakyat Syariah pada bulan Maret 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 9 publications
0
4
0
2
Order By: Relevance
“…significant. Further research by (Rolianah & Sari, 2021) found that the ROA and NPF values did not have a significant difference while the FDR and BOPO ratios had a significant difference between before and during the covid 19 pandemic at Islamic People's Financing Banks. The research of (Kadir & Rahman, 2021) found that the overall impact of covid 19 on the financial performance of Islamic BPR in Indonesia had a significant effect on the NPF and FDR variables.…”
Section: Eduvest -Journal Of Universal Studiesmentioning
confidence: 89%
“…significant. Further research by (Rolianah & Sari, 2021) found that the ROA and NPF values did not have a significant difference while the FDR and BOPO ratios had a significant difference between before and during the covid 19 pandemic at Islamic People's Financing Banks. The research of (Kadir & Rahman, 2021) found that the overall impact of covid 19 on the financial performance of Islamic BPR in Indonesia had a significant effect on the NPF and FDR variables.…”
Section: Eduvest -Journal Of Universal Studiesmentioning
confidence: 89%
“…Aktiva neraca dan aktiva administratif telah dibobot sesuai tingkat bobot siko yang telah ditentukan. Tujuan ATMR adalah untuk mengendalikan pertumbuhan aset bank yang memberikan return tinggi dengan resiko rendah (Rolianah & Sutono, 2021).…”
Section: Roa = (Laba Bersih/total Aktiva) X 100%unclassified
“…According Rachmad and Fitria (2021) that CAR during the Covid-19 pandemic is better than CAR before the Covid-19 pandemic in Islamic bank. In other study, during the pandemic CAR indicator of Sharia rural bank are still accordance with Financial Services Authority standar (Hassan, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Conversely, if NPF ratio is high or Islamic rural bank financing is dominated by non-performing quality, then the EAQ ratio will deteriorate (Otoritas Jasa Keuangan, 2019). Rolianah et al (2021) stated that REO shows a significant impact before and during the pandemic. The conclusion is countercyclical policies have an effect on REO.…”
Section: Literature Reviewmentioning
confidence: 99%